Akta Notaris Sebagai Alat Bukti Tertulis Yang Mempunyai Kekuatan Pembuktian Yang Sempurna - Rif'ah Roihanah (Justicia Islamica, 2012)
In Indonesia, the setting of the Institute of Notary regulated in Law No. 30 of 2004 Undang-undang Jabatan Notaris (UUJN). Based UUJN can be explained that the notary is a public official authorized to make the deed which the deed is a deed that is authentic. An authentic act can be divided further into deed made by the officials and the deed made by the parties. To be classified as a deed of a letter must have the signature as required in article 1869 Civil Code. So the function signature is none other than to characterize or to mengindividualisir a certificate can be viewed as the identification of signatures affixed to the deed. In order to act as evidence has the force of proof writing is perfect, then the deed must qualify the authenticity of which is determined by law, one of which must be made by or before the authorities. In the event must be made by the competent authority or before the notary profession is a very important role in fulfilling the terms of the authenticity of a letter or certificate that has the perfect strength of evidence (Article 1 UUJN). Perfect proof of the power contained in an authentic act is a blend of some of the strength of evidence and the requirements contained him. The absence of any proof or strength of these requirements will result in an authentic deed has no evidentiary value of the power of the perfect (volledig) and binding (bindende) so that the deed will lose their authenticity and no longer an authentic deed. In an authentic deed must satisfy (i) the strength of proof of birth, (ii) Strength Formal Verification and (iii) The power of the Material Evidence. Then apart from the strength of evidence is based UUJN that a notary has the authenticity requirement, then at the deed must be (i) The penghadap who are qualified (minimum of 18 years or have been married and legally competent) facing the Notary in the working area notary public is concerned, (ii) The penghadap must be known to the notary or introduced to it by 2 (two) witnesses identification of at least 18 years old or have been married and legally competent or introduced by 2 (two) other penghadap; (iii ) The penghadap express intention; (iv) the purpose of the Notary mengkonstatir penghadap in a deed, and (v) the notary read the wording in the deed to the penghadap and was attended by 2 (two) witnesses who meet the requirements, and (vi) Immediately after the deed was read the penghadap, witnesses and the notary then affix his signature, which means justify what is contained in the deed, and the signing must be done at that time.